Analysis of Village Fund Management in Improving Village Development in Rawak Hulu Village - Agustin, Peni; Haryono, Haryono (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
With the change in the paradigm system, the village community is becoming increasingly aware of the way the village government performs, starting from the local government to the smallest village government. The purpose of this research is to deepen the understanding of the management of the Village Fund by the Rawak Hulu Village government and evaluate its compliance with existing regulations. This research applies a qualitative approach with descriptive methods, using data collection techniques in the form of observation, interviews, and documentation studies. This research used primary and secondary data, where primary data was obtained through direct interviews with the Rawak Hulu Village Secretary. While secondary data contains data on the Financial Report on the Realization of the Rawak Hulu Village APBDes in 2023. The results of this study indicate that in terms of Village Fund Management carried out in increasing village development by the Rawak Hulu Village government, it is in accordance or realized with the plans that have been implemented because every year there are goals from the planning process that are consistent because they have been made which are placed through the Village Medium Term Development Plan.